Fetal dystocia due to muscular steatosis coupled with ascites and arthrogryposis in Mehsana buffalo - Chauhan, P. M.; Kapadia, P. S. (Animal Reproduction Update, 2022)
A four-year-old primiparous Mehsana buffalo at full term of gestation suffering from dystocia was presented to Veterinary Clinical Complex, Deesa. Per-vaginal examination of the dam identified the presence of both forelimbs and fetal head at the dilated birth passage. The excessive bulging of the neck regions occupied the pelvic inlet of the dam, causing severe feto-maternal disproportion. The large male fetus was delivered dead via caesarean operation. Examination of the fetus identified bilateral enlargement of the cervical and shoulder region along with ascites and arthrogryposis. Microscopically, the musculature of cervical and shoulder regions was replaced by massive adipose and fibrous connective tissue. The fetus was diagnosed with muscular steatosis with ascites based on gross and microscopic features. The buffalo recovered uneventfully after five days of post-operative treatment.
Keywords: Ascites; Buffalo; Dystocia; feto-maternal disproportion; steatosis